Strengthening Quality in The Pre-Analytical Phase of Laboratory Medicine: The Role of Quality Indicators - Singh, Natasha; Rawat, Anamika; Priya, Ritu; Mittal, Ankita; Chandel, Vaibhav; Mishra, Jyoti (Journal of Neonatal Surgery, 2025)
Laboratory medicine has undergone substantial advancements over the past decades, particularly in the analytical phase, with the integration of automation, quality control, and advanced diagnostic technologies. However, the pre-analytical phase remains a critical area prone to errors, contributing to nearly 70% of total laboratory mistakes. Errors occurring before a sample reaches the laboratory, termed the 'pre-analytical phase', are often overlooked despite their significant impact on patient safety and diagnostic accuracy. Quality indicators (QIs) are essential for monitoring and improving the pre-analytical phase of laboratory testing, ensuring accuracy and efficiency. The International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) has developed specific QIs to standardize and enhance this phase, reducing errors in sample collection, transport, and processing. Implementing these indicators in clinical practice helps laboratories track performance, identify weaknesses, and optimize workflows. By focusing on the QIs, from their lab, one can improve patient safety, diagnostic reliability, and overall laboratory efficiency. Standardized QIs contribute to better healthcare outcomes and reinforce the importance of quality control in laboratory medicine. This article focusses on the Qis followed in the Central Laboratory with analysis of these QIs, root cause analysis (RCA) and corrective and preventive actions (CAPA) of the non-conformities